Determinan Persepsi Ibu Hamil Terhadap Senam Dan Yoga Prenatal Di Masa Pandemi Covid-19 - Syaripah, Rosita; Marlina, Endah Dian (Jurnal Kebidanan Malakbi, 2023)
Pregnant women are a group of people who are vulnerable to infection with the Covid-19 virus. The COVID-19 pandemic has caused restrictions on routine health services including maternal and neonatal health services so optimal physical activity is needed in the form of prenatal exercise and yoga that can be done at home to improve maternal fitness as a form of increasing immunity for pregnant women. The purpose of this study was to determine the perception of pregnant women on prenatal exercise and yoga during the COVID-19 pandemic. This study used a cross-sectional design from July – September 2022. The sample of this study was 100 people, taken by random sampling, the data were analyzed by Chi-square. The variables related to the perception of the vulnerability of pregnant women to exercise and yoga during the COVID-19 pandemic were income with a P value (0.05) and the amount of parity (p-value 0.01), as well as the determinant of the perception of the benefits of pregnant women's behavior, namely the type of education (p Value 0.045), it can be concluded that there is a relationship between income, parity ,and education on the perception of pregnant women towards Prenatal gymnastics and yoga during the COVID-19 pandemic at Karang Kitri Public Health Center and Mustika Jaya Health Center Bekasi City